Taxonomic study and diversity of Postia s.lat. in Swat, Pakistan: addition of five brown rot Polypores to the country - Hussain, Shahid; Nisar, Mohammad; Sher, Hassan (Archives of microbiology, 2024)
Brown rot Polypores are ecologically significant as they play a crucial role in maintaining the carbon cycle and contribute to humus formation in forest ecosystems through their lignocellulose degradation ability. It is important to note that some species can significantly impact timber, potentially causing decay in economically valuable wood. Many Asian countries including Pakistan are still under the exploratory phase and have undocumented species diversity in Polypore fungi. In the current study, collections representing five different species belonging to two families, Postiaceae and Adustoporiaceae, were subjected to detailed morphoanatomical and molecular analyses. A combined matrix of two gene datasets (ITS and nrLSU) was analyzed using three different phylogenetic methods viz. Maximum Parsimony (MP), Maximum Likelihood (ML), and Bayesian inference (BI). Our study presents descriptions of five previously undocumented brown rot Polypore species from the country including Fuscopostia fragilis (Fr.) B.K. Cui, L.L. Shen & Y.C. Dai, Amaropostia stiptica (Pers.) B.K. Cui, L.L. Shen & Y.C. Dai, Cyanosporus piceicola B.K. Cui, L.L. Shen & Y.C. Dai, Spongiporus balsameus (Peck) A. David, Rhodonia placenta (Fr.) Niemelä, K.H. Larss. & Schigel. Regarding the molecular data, nodes of our subject sequences were substantially supported and fell under their respective species clades with high ML bootstrap values (≥ 95), MP bootstrap ≥ 74 and BI probabilities ≥ 0.98. Findings of the study will not only contribute to our understanding of local Polypores species diversity but also enhance knowledge of geographical distribution in global context.